Women of Will for Nation Building in Pramoedya’s Three Early Novels - Dewi, Novita (Archīum Ateneo, 2024)
Of great interest to Pramoedya’s writing, which is largely neglected, is the presence of ordinary women as supporting characters. This paper discusses the depiction of strong- willed women who embody the desired character that the Indonesian nationalists in the 1950s sought to construct in Pramoedya’s three early novels, i.e. Keluarga Gerilya [The Guerilla Family] (1950), Korupsi [Corruption] (1954), and Sekali Peristiwa di Banten Selatan [Once Upon A Time in South Banten] (1958). Written during the period when nationalism in the country began to crack, the three novels present minor but arresting female characters: these women are able to find their right place in society as to excel and sometimes surpass men. Indeed, it is the presence of the characters that gives power to the narrative – that of a nation in decline. Using Fredric Jameson’s interpretation of politics and literature as theoretical departure, this paper examines the novels against the backdrop of Indonesian social history after the first decade of independence. It is revealed that the presence of these female characters is not only allegorical to the Indonesian political reality of the day, but it also harbors aspirations and ideal visions of what future Indonesian society should be like.